(untitled) (Philippines, 1999)
Proving the knowledge base for improved policy choices leading to economic growth, poverty alleviation and environmental sustainability ,...
Keywords: Fisheries,Fishery management,Nghiên cứu thủy sản; Research,Government policy; Developing countries